PENGGUNAAN LULUR ZAITUN TERHADAP PERAWATAN KULIT TUBUH - Hari, Sari Neng; Rostamailis, Rostamailis; Astuti, Murni (Journal of Home Economics and Tourism, 2015)
This study aims to describe the effect of the use of the olive scrub of skin care body. This study is based on an indicator of changes in skin moisture and brightness of the skin. The study is in the form of pre-experimental design with a one-group pretest-posttest. The object of this research are manifold body skin dry, while the sample in this study were women who have the same age range which ranges between 18 and 25 years who have dry skin with moisture levels below 38%. Data collected from this research is primary data obtained directly from the sample by filling out the assessment form has been provided. The research data were analyzed using tests of normality, homogeneity and t-test. Based on the results of the data, proving that the use of olive scrub showed significant results for each indicator with the results of the normality test the magnitude of the numbers of significance (0.214) > Î± = (0.05) means that the data are normally distributed, homogeneity test results f count (4) <f Table (5.39), followed by t-test with the results of the t (-19.000) and t table (-2.776). This means that there is a significant effect on the body skin care with the use of olive scrub.Keywords: Olive scrubs, body skin care.